Culling Trends on a Hungarian Large Scale Dairy Farm - Violetta Tóth; Virág Nagypál; Ágnes Süli; Edit Mikó (Scientific Papers Animal Science and Biotechnologies, 2023)
Different diseases experienced in dairy farms cause decreased productivity and profitability. When a decision is made regarding culling, age, phases of lactation cycle, milk production, reproduction phase and health stage all have to be taken into account. Main reasons of culling are reproduction disorder, mastitis, low milk production and lameness. Based on 5-year data of the farm of this research, main culling reasons were identified. Another aim of this study was to find out in which lactation culling had the highest proportion and why. A number of 1175 cows left the farm as a result of culling during 5-year period. Thirty percent of cullings was caused by udder diseases and 22% of cullings occurred due to reproduction disorder. Twelve percent of culling was caused by the sum of low milk production, lameness and metabolic diseases. Thirty five percent of culling was caused by other diseases (lung-inflammation, heart defect, heat stress) and managerial decisions. Culling trends in each lactation: 23 % in first, 32 % in second, 25 % in third, 12 % in fourth, 8 % in 4< (5., 6., 7. and 8.) lactations. In the first lactation the main reasons of culling were reproduction disorder (7.74 %), udder diseases (4.94 %) and low production (4.5 %). However, in the second lactation the highest culling ratio was caused by udder diseases (8.77 %), lower by reproduction disorder (7.83 %) and the lowest by low production (2.8 %). In the third lactation udder diseases (8.43 %), low production (5 %) and reproduction disorder (4.09%) was the distribution between the different factors causing culling.